Pregnancy in sickle cell thalassemia: double trouble! - N., Sunanda; Impana M., (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
This is a case report of 20-year-old multigravida (G2P1L0) belonging to tribal community presented at 30 weeks of gestation with severe anemia, fever, arthralgia and jaundice with multiple blood transfusions in the past and with previous pregnancy outcome being stillborn and was not evaluated for the same. A diagnosis of sickle cell β+Thalassemia (SCD crisis) was made and managed vigilantly by multidisciplinary approach and had full term vaginal delivery with good perinatal outcome and finally both mother and newborn were discharged in stable condition. This highlights the overall increase in maternal and fetal complications in pregnancy with sickle cell thalassemia. Thus health education, screening, early intervention with multidisciplinary approach and regular follow up prevents maternal morbidity and mortality.